Body mapping of sweating patterns in male athletes in mild exercise-induced hyperthermia - Smith, C. J.; Havenith, G. (European Journal of Applied Physiology, 2011)
Regional variation in sweating over the body is widely recognised. However, most studies only measured a limited number of regions, with the use of differing thermal states across studies making a good meta-analysis to obtain a whole body map problematic. A study was therefore conducted to investigate regional sweat rates (RSR) and distributions over the whole body in male athletes. A modified absorbent technique was used to collect sweat at two exercise intensities [55% (I1) and 75% (I2) VO2max] in moderately warm conditions (25°C, 50% rh, 2 m/s air velocity). At I1 and I2, highest sweat rates were observed on the central (upper and mid) and lower back, with values as high as 1,197, 1,148, and 856 g/m-2/h, respectively, at I2. Lowest values were observed on the fingers, thumbs, and palms, with values of 144, 254, and 119 g/m-2/h, respectively at I2. Sweat mapping of the head demonstrated high sweat rates on the forehead (1,710 g/m-2/h at I2) compared with low values on the chin (302 g/m-2/h at I2) and cheeks (279 g/m-2/h at I2). Sweat rate increased significantly in all regions from the low to high exercise intensity, with exception of the feet and ankles. No significant correlation was present between RSR and regional skin temperature (T sk), nor did RSR correspond to known patterns of regional sweat gland density. The present study has provided detailed regional sweat data over the whole body and has demonstrated large intra- and inter-segmental variation and the presence of consistent patterns of regional high versus low sweat rate areas in Caucasians male athletes. This data may have important applications for clothing design, thermophysiological modelling and thermal manikin design.